Potential of electrospun core–shell structured gelatin–chitosan nanofibers for biomedical applications. (20th January 2016) - Jalaja, K.; Naskar, Deboki; Kundu, Subhas C.; James, Nirmala R.
Graphical abstract: Highlights: Core–shell nanofibers with chitosan as shell is developed using gelatin as core. No synthetic template and harsh solvent are used for chitosan nanofiber production. Cross-linking is achieved using modified polysaccharide and disaccharide. Exhibited an excellent adhesion and proliferation of osteoblast cells. Abstract: Coaxial electrospinning is an upcoming technology that has emerged from the conventional electrospinning process in order to realize the production of nanofibers of less spinnable materials with potential applications. The present work focuses on the production of chitosan nanofibers in a benign route, using natural polymer as core template, mild solvent system and naturally derived cross-linkers. Nanofibers with chitosan as shell are fabricated by coaxial electrospinning with highly spinnable gelatin as core using aqueous acetic acid as solvent. For maintaining the biocompatibility and structural integrity of the core–shell nanofibers, cross-linking is carried out using naturally derived cross-linking agents, dextran aldehyde and sucrose aldehyde. The biological evaluation of gelatin/chitosan mat is carried out using human osteoblast like cells. The results show that the cross-linked core–shell nanofibers are excellent matrices for cell adhesion and proliferation.